Not Lost in Translation: How Study of Diseases in Our Pets Can Benefit Them and Us - Henry, Carolyn J. (Mo Med, 2013)
Practice-changing medical discovery requires preclinical and clinical assessment be carried out using appropriate disease models. There is growing awareness of companion animals with naturally-occurring disease as such models. They offer significant advantages over more traditional in vivo models of induced disease. This review describes current efforts to promote translation of discoveries between human and veterinary medicine in order to more rapidly and efficiently make progress in improving the health of all human and animal patients.